Worldwide Invasions of Centrarchidae: The Dark Side of the Sunfish Family - Neil Angelo Abreo; Jonathan Tibo; António Barbosa Nogueira; Athanasios Nikolaou; Cüneyt Kaya; Ali Serhan Tarkan; Irmak Kurtul; Stelios Katsanevakis; Ronaldo Sousa; Teun Everts; Emili García‐Berthou; John S. Hargrove; et al. (Fish and Fisheries, 2026)
Freshwater fish invasions are major drivers of global ecological change, disrupting native biodiversity and ecosystem functions. However, many invasive fish hold significant socioeconomic value, resulting in conflict over their management. Centrarchidae, which are globally distributed and are important for sportfishing and aquaculture, are now potentially becoming a global threat. Yet, no comprehensive appraisal exists across taxa and regions integrating taxonomy, pathways, impacts and risk analysis for Centrarchidae. To address these gaps, we compiled published literature and leveraged publicly available databases to critically evaluate the current global status of non‐native Centrarchidae, finding 30 species established outside their native ranges with 17 being outside of North America. Largemouth bass ( Micropterus nigricans ) and pumpkinseed ( Lepomis gibbosus ) are the most widely introduced centrarchids. Reported impacts of Centrarchidae introduction are mostly ecological, with predation, competition, hybridisation, and disease transmission as major mechanisms. Conversely, socio‐economic and cultural effects are underreported. Currently, only ten species have undergone rapid risk screening, with 90% flagged as high risk. However, risk analyses remain sparse, confounded by taxonomic uncertainties (including hybridisation) and context dependence of impacts. With the changing climate and other anthropogenic disturbances in freshwaters, habitat suitability is expanding for centrarchids. Although concerning, Centrarchidae form a highly human‐mediated invasion complex with predictable pathways and tractable leverage points, so limiting propagule pressure and standardizing assessments can curb their future spread while informing balanced and evidence‐based fisheries policy that reconciles socioeconomic benefits with environmental costs.

First documented black seabream (Spondyliosoma cantharus) nesting aggregation in the Mediterranean Sea - Jennifer C. A. Pistevos; Athanasios Nikolaou; Ivan T. Petsimeris; Giulia Pitarra; Nicola Greggio; Olympos Andreadis; Thomas Hasiotis; Antonios D. Mazaris; Stelios Katsanevakis (Environmental Biology of Fishes, 2026)

Multimodal Underwater Sensing of Octocoral Populations and Anthropogenic Impacts in a Conservation-Priority Area (NE Aegean Sea, Greece) - Maria Sini; Jennifer C. A. Pistevos; Angeliki Bosmali; Artemis Manoliou; Athanasios Nikolaou; Giulia Pitarra; Ivan T. Petsimeris; Olympos Andreadis; Thomas Hasiotis; Antonios D. Mazaris; Stelios Katsanevakis (Journal of Marine Science and Engineering, 2025)
Coralligenous assemblages are among the most diverse habitats of the Mediterranean Sea, yet those of the north-eastern basin remain understudied despite their vulnerability to human impacts and climate change. We applied a multimodal underwater sensing approach to map coralligenous formations, assess gorgonian populations and evaluate the effects of marine litter in a conservation-priority area (NE Aegean Sea, Greece). Side-scan sonar enabled seafloor mapping and guided targeted Remotely Operated Vehicle (ROV) surveys. ROV-based distance sampling and imagery provided quantitative data on Eunicella cavolini and Paramuricea clavata, including density, size structure, and injuries, alongside systematic documentation of marine litter. Gorgonians formed monospecific ecological facies, segregated by location—P. clavata occurred deeper than E. cavolini. Densities were low (E. cavolini: 0.35 colonies m−2, P. clavata: 1.46 colonies m−2) and small colonies (

Pinna nobilis refugia breached: Ongoing Mass Mortality Event in the Gulf of Kalloni (Aegean Sea) - ATHANASIOS NIKOLAOU; EVANGELOS PAPADIMITRIOU; ELLI KIOURANI; STELIOS KATSANEVAKIS (Mediterranean Marine Science, 2024)
The endemic Mediterranean fan mussel Pinna nobilis is on the brink of extinction due to an infectious disease that has caused an ongoing Mediterranean Mass Mortality Event (MME) since 2016. Currently, healthy P. nobilis populations can only be found in a few refuges, mainly transitional waters such as coastal lagoons and estuaries. In the eastern Mediterranean, the only remaining fan mussel population is located in the Gulf of Kalloni (Lesvos Island, Greece). This study reports on a severe mortality event that occurred during summer 2023, leaving the population decimated and limited mainly to young individuals. The estimated density of live individuals dropped from 1.22 to 0.23 individuals per 100 m², indicating an 81% population decline within approximately three months. The significant reduction in the P. nobilis population in the Gulf of Kalloni highlights the ongoing threat of MMEs. Continuous monitoring of P. nobilis and environmental variables, such as temperature and salinity, enhanced protection from anthropogenic pressures, and research into disease resistance mechanisms are crucial for the conservation of this critically endangered species.

Distribution, health and threats to Mediterranean macroalgal forests: defining the baselines for their conservation and restoration - Jana Verdura; Lluc Rehues; Luisa Mangialajo; Simonetta Fraschetti; Zahira Belattmania; Silvia Bianchelli; Aurélie Blanfuné; Brahim Sabour; Antonia Chiarore; Roberto Danovaro; Erika Fabbrizzi; Sylvaine Giakoumi; et al. (Frontiers in Marine Science, 2023)
The worldwide decline of macroalgal forests is raising major concerns for the potentially negative consequences on biodiversity and ecosystem functions, pushing for the definition of specific conservation and restoration measures. Protecting and restoring these habitats requires detailed information on their distribution, ecological status, and drivers of decline. Here, we provide the most updated available information on the distribution of Mediterranean Cystoseira s.l. forests by conducting a comprehensive bibliographic survey of literature published from 2009 to 2021, complemented by unpublished data. We also provide insights into the ecological status of these forests and the stressors affecting them across the Mediterranean basin. Our results show that most Mediterranean coasts remain un(der)studied and that the available information is concentrated in spatially limited coastal areas, restricted to very few species. When the ecological status is reported, data is highly heterogeneous, making any comparisons problematic, what claims for the description and use of easy and standardized monitoring methods for comparative purposes. Drivers of decline of Cystoseira s.l. forest have been even less investigated and, therefore, still poorly characterized. Our results highlight that our current knowledge is still insufficient to implement effective conservation and restoration strategies at the basin scale but also regionally. We call for the urgent need for mapping and standardized monitoring of Cystoseira s.l. forests to obtain baseline information for future management strategies involving their conservation, the mitigation of the stressors threatening them and the restoration of the degraded forests.

Marine extinctions and their drivers - Athanasios Nikolaou; Stelios Katsanevakis (Regional Environmental Change, 2023)
A literature review was conducted to investigate marine global and local extinctions and their drivers; the review followed the PRISMA-EcoEvo guidelines. The data extracted was enhanced with status assessments from the IUCN Red List. We recorded local extinctions for 717 species, of which 18 were global extinctions. Most of these extinctions were recorded on very localized and sub-ecoregion scales. The taxonomic group with the most reported local extinctions was molluscs (31%), followed by cnidarians (22%), fish (17%) and macroalgae (15%). The dominant drivers of extinction differed by taxonomic group. High mobility taxa were driven extinct mainly by overexploitation, whereas low mobility taxa from pollution, climate change and habitat destruction. Most of these extinctions were recorded in the Temperate Northern Atlantic (41%) and the Central Indo-Pacific (30%). Overexploitation was historically the primary driver of marine local extinctions. However, in the last three decades, other drivers, such as climate change, climate variability, and pollution, have prevailed in the published literature. Half of the reported extinctions were of species not assessed by the IUCN Red List, and 16% were species in threatened categories. Global extinctions in the marine environment were mainly attributed to overexploitation, followed by invasive species, habitat destruction, trophic cascades, and pollution. Most extinctions reported in the literature were derived from low-confidence data. Inadequate monitoring may lead to false reports of extinctions or silent extinctions that are never reported. Improved conservation and restoration actions are urgently needed to halt biodiversity loss.

Microbiological stability and sensorial valorization of thyme and oregano essential oils alone or combined with ethanolic pomegranate extracts in wine marinated pork meat - Ioanna Mantzourani; Maria Daoutidou; Anastasios Nikolaou; Yiannis Kourkoutas; Athanasios Alexopoulos; Ilias Tzavellas; Marilena Dasenaki; Nikolaos Thomaidis; Stavros Plessas (International Journal of Food Microbiology, 2023)

Environmental Information, Asymmetric Information, and Financial Markets: A Game-Theoretic Approach - Ioannis E. Nikolaou; Athanasios Chymis; Konstantinos Evangelinos (Environmental Modeling & Assessment, 2013)